2007
DOI: 10.1103/physrevlett.98.152001
|View full text |Cite
|
Sign up to set email alerts
|

Compton-Scattering Cross Section on the Proton at High Momentum Transfer

Abstract: Cross-section values for Compton scattering on the proton were measured at 25 kinematic settings over the range s=5-11 and -t=2-7 GeV2 with a statistical accuracy of a few percent. The scaling power for the s dependence of the cross section at fixed center-of-mass angle was found to be 8.0+/-0.2, strongly inconsistent with the prediction of perturbative QCD. The observed cross-section values are in fair agreement with the calculations using the handbag mechanism, in which the external photons couple to a singl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…Although it was not possible to actually measure the Compton background contribution from the data of this experiment, a reasonable estimate was obtained by extrapolating from the data of [130] using the empirical s −8 scaling behavior of dσ/dt, which showed that the Compton scattering background, while irreducible, was safely below the level where it could significantly impact the form factor ratio results.…”
Section: Proton δ-θ Correlationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it was not possible to actually measure the Compton background contribution from the data of this experiment, a reasonable estimate was obtained by extrapolating from the data of [130] using the empirical s −8 scaling behavior of dσ/dt, which showed that the Compton scattering background, while irreducible, was safely below the level where it could significantly impact the form factor ratio results.…”
Section: Proton δ-θ Correlationmentioning
confidence: 99%
“…The authors of [130] found a scaling behavior of s −8 for the Compton scattering cross section at fixed momentum transfer, to be contrasted with the approximate s −7 scaling of the photoproduction cross section found in [129]. Although it was not possible to actually measure the Compton background contribution from the data of this experiment, a reasonable estimate was obtained by extrapolating from the data of [130] using the empirical s −8 scaling behavior of dσ/dt, which showed that the Compton scattering background, while irreducible, was safely below the level where it could significantly impact the form factor ratio results.…”
Section: Proton δ-θ Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…The remainder, the "reduced" cross section, is assumed to be independent of the substructure of the nucleons. This 5) for the process γ(N 1 N 2 ) → N 1 N 2 , where t i is the square of the four-momentum transfer to nucleon N i . The ratio of cross sections for γ(pp) → pp and γ(pn) → pn is then given by the ratio of nucleon form factors squared,…”
Section: Photodisintegration Of the Deuteronmentioning
confidence: 99%